Penerapan Sanksi Pidana Terhadap Pelaku Tindak Pidana Manipulasi dan Penciptaan melalui Akun Media Sosial Facebook - Agie Rinaldy Maizuly; Bambang Hartono; Indah Satria (Prodi Ilmu Hukum, Universitas Teuku Umar, 2022)
The development of the internet which is increasing both in technology and its use, has made crimes that were originally conventional such as threats, theft and fraud can now be carried out by using computer media online with a very small risk of being caught. cases of fraud by manipulating someone's data or using someone's name to carry out their fraudulent actions through Facebook and Whatsapp online media occurred in the Lampung Province area. This study was conducted to identify and explain the factors that cause perpetrators to commit criminal acts of manipulation and creation through Facebook social media accounts and how to implement criminal sanctions. This research is a normative juridical research that wants to identify the background aspects and the application of criminal sanctions. The data used consists of primary legal materials, secondary legal materials, and tertiary legal materials. The results showed that the factors causing the perpetrators to commit criminal acts of manipulation and creation through Facebook social media accounts were environmental factors, lack of social control, community interests, people's ignorance, facilities, facilities, technological progress and psychological factors. The application of material criminal sanctions against the perpetrators of the criminal act of manipulation and creation through the Facebook social media account that was applied was appropriate because the elements of a criminal act were proven.